Design of a Corrective Feedback Software for Coffee Growers in the Department of Cauca Using a User-Centered Design Methodology (UCD) - Moncayo Marulanda, Luis Fernando; González Serrano, Carolina (I+ T+ C- Research, Technology and Science, 2024)
Considering the relevance of the coffee industry for Colombia and specifically for the department of Cauca and because of the sustainability challenges that the industry presents in the department, the article presents the design process, using a UCD methodology, a digital platform that aims to contribute to improving the quality of coffee in the department of Cauca, Colombia. An agile and iterative software design methodology is used to provide effective solutions to the needs of the different identified users. As a result, a software design is obtained that contains user history, use cases, sequence of use, data structure and evaluation. Using modern and flexible technologies such as TypeScript, React and React DO, a prototype was developed to be evaluated with coffee tasters in Cauca who expressed an understanding and interest in the exposed platform. In conclusion, the agile UCD Software design methodology proved to be effective. Furthermore, it is concluded that the implementation of this platform would represent an important contribution to the Cauca coffee industry, promoting best practices to increase the profits of coffee growers and strengthen regional competitiveness. It is suggested that future research explore the adoption of the platform in other coffee-growing regions of Colombia and internationally